Insurance against Climate Change : Financial Disaster Risk Management and Insurance Options for Climate Change Adaptation in Bulgaria - World Bank Group (Washington, DC, 2014)
Bulgaria is exposed to nearly all types of climate extremes, including floods, droughts, and others, as well as earthquakes. The combination of insurance products, early warning systems, information campaigns, infrastructure adaptation measures, and strict regulations can be very useful in tackling the negative climate change impacts. This note provides an overview of the insurance sector s contribution to climate change - related risk prevention and highlights some of Bulgaria s ongoing disaster risk management (DRM) efforts. The note aims to raise awareness and emphasize the role that financial disaster risk management (FDRM), including insurance, can have in climate change adaptation. Based on a desk review and preliminary in-country stakeholder consultations, the note s findings are meant to motivate new thinking and serve as an engagement tool for ongoing in-country discussions, as well to help identify analytical work to be carried out in the future. Based on the preliminary review of Bulgaria s specific context, several ideas are being put forward to be further explored in the ongoing discussions toward creating FDRM products to address the major natural disasters (in particular, floods, droughts, and earthquakes) and improving adaptation to climate change. Potential areas of analysis that can be further explored and, as such, plant a seed for future action can focus on promoting risk prevention and deploying insurance instruments, including issues around traditional risk management, technology innovation, compulsory disaster insurance, forecast insurance, and disaster insurance pools. The analysis which will assess the extent of vulnerability of the subjects covered by existing insurance products, can subsequently lead to the decisions on priority insurance products to be introduced in the future.